Sequential mediation analysis of workplace bullying, work-life conflict, and young employees’ outcomes in Vietnam - Hoang-Khang Du; Hai-Ninh Do (Asian Academy of Management Journal, 2023)
There has been a growing focus on workplace bullying, especially in emerging countries. This study examines the impact of workplace bullying on young employees’ outcomes in Vietnamese firms. Based on the conservation of resources theory, a sequential mediation model of five constructs (workplace bullying [WPB], work-life conflict [WLC], job satisfaction [JS], work support, and negative well-being [NWB]) was studied. Data from 238 young employees of different sectors was used to test the hypothesised model. The research data were analysed using AMOS version 22 to examine the constructed hypotheses. The results confirm that bullying is, directly and indirectly, related to employees’ outcomes in terms of job satisfaction and NWB. Furthermore, the mediating effects of WLC on the relationships of bullying, job satisfaction, and NWB are confirmed. Contrary to previous research, work support did not mediate these relationships. In order to lessen the level of perceived NWB, it is essential to reduce negative acts at work as well as enhance the understanding of this phenomenon. This study contributes to the research literature on bullying in Vietnamese context, both theoretically and practically. From these findings, organisations might be beneficial from this study to reduce the level of workplace bullying. Further research could navigate which constructs could enhance young employees’ positive experience at work in the face of workplace bullying.